PERENCANAAN PERKUATAN TEBING PADA RUAS JALAN MALANG - KEDIRI STA ( 30KM ) DENGAN MENGGUNAKAN DINDING PENAHAN TANAH TIPE KANTILEVER DI DESA KAWADEN, KECAMATAN NGANTANG, KABUPATEN MALANG - Nenohai, Imanuel F; Rasidi, Nawir; Hanggara, Ikrar (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Retaining wall is one of the structures that serves to maintain the stability of a landfill, so the heap is not moving or landslides. This building is mostly used in irrigation projects, highways, ports and others. In general, the use of retaining walls in the field consists of two types of gravity type and cantilever type. The main difference between the construction of these two types of retaining walls is that of the cantilever type, whereas the type of gravity does not use reinforcement. In terms of use, the cantilever type is more widely used for slopes that have a height of more than 6 meters, while the gravity type is used for altitudes less than 6 meters. The stability of the retaining wall can be expressed by the value of Fs (safety factor). The value of the security factor under consideration is Fs Overtuning which is the security factor to the rolling force, Fs Slading is the safety factor of the shear, Fs bearing capacity is the safety factor to the collapse of carrying capacity. Therefore, the purpose of this study is to know the efficiency of the base width of cantilever type cantilever wall on Abd.Manan Wijaya Road which is located in Kaweden Village, Ngantang District, Malang Regency so that it is stable to the style of bolsters, shear and soil bearing capacity. After the calculation, the result of stability factor to shear 1.61> 1.5 (safe), stability to bolsters 2.0> 1.5 (safe), Stability Against soil bearing capacity 142,795> qa = 123.39 kN / M2. Then it can be concluded that the condition of cantilever cantilever wall stability is safe against danger of bolsters, shear and soil bearing capacity. Keywords: Cantilever Wall Retaining Wall, Base width efficiency, Stability